2013
DOI: 10.5430/rwe.v4n2p43
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Capital on Economic Growth: Empirical Evidence from Sudan

Abstract: This paper empirically investigates the impact of human capital on economic growth in Sudan for the period 1982-2009 by using a simultaneous equation model that links human capital i.e. school attainment; and investment in education and health to economic growth, total productivity, foreign direct investment, and human development index. Based on three-stage least squares technique, the empirical results of the paper show that quality of the education has a determinant role in the economic growth; health quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
1
7
1
1
Order By: Relevance
“…Thus, our results in part do not confirm Elwasila Saeed Elamin (2017a) who found a positive relationship between health and economic growth in Sudan, when considered in isolation of resource rents. Also, our results contradict Arabi and Abdalla (2013) who found that school attainment and health have positive and significant effects on economic growth in Sudan. However, our results are in line with Akpan and Chuku (2014) who found the negative effect of resource abundance on human capital accumulation in Nigeria through the channels of the DD and crowding out of human capital effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, our results in part do not confirm Elwasila Saeed Elamin (2017a) who found a positive relationship between health and economic growth in Sudan, when considered in isolation of resource rents. Also, our results contradict Arabi and Abdalla (2013) who found that school attainment and health have positive and significant effects on economic growth in Sudan. However, our results are in line with Akpan and Chuku (2014) who found the negative effect of resource abundance on human capital accumulation in Nigeria through the channels of the DD and crowding out of human capital effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies also revealed that the effect of FDI on economic growth depend on the level of human capital (Abdalla, 2013;Sukar & Hassan, 2007;Borensztein, 1998). Recently, UNCTAD (2013) and other studies (Sala & Trivin, 2014;IMF, 2009) suggest that the positive effect of FDI depend on openness to international trade.…”
Section: Empirical Literaturementioning
confidence: 97%
“…Again, the growth impact of FDI with and without other important covariates will not be the same. Indeed, literature recognizes the role of factor interdependences in influencing economic growth (UNCTAD, 2012Abdalla, 2013). For example, well developed infrastructure attracts more foreign firms than otherwise; availability of competent human capital speeds he return from investment, etc, ceteris paribus.…”
Section: Additional Modelsmentioning
confidence: 99%
“…Therefore, under normal circumstances, the increase in PDRB causes greater government revenue, as well as greater government spending. Development expenditure has a positive impact on Gross Domestic Product (GDP) growth, which suggests that investment in development can support economic growth [28,[50][51][52]. Furthermore, results show that investing in infrastructure can accelerate economic growth.…”
Section: Discussionmentioning
confidence: 99%